Odpowiedzi

2009-12-01T19:17:34+01:00
8(7-4y)-7(4y+1)+5(8y-1)=19
56-32y-28y-7+40y-5-19=0
-20y+56-31=0
-20y+25=0
-20y=-25/:(-20)
y=25/20=5/4

b)3(2x+1)-5(12x-7)+7(6x-1)=23
6x+3-60x+35+42x-7=23
-12x+31=23
-12x=23-31
-12x=-8/:(-12)
x=8/12=2/3
c)0.2x+0.5x+5(5x-1)-2.7x=6.5
0,2x+0,5x+25x-5-2,7x=6,5
23x=6,5+5
23x=11,5/:23
x=0,5
d)0.3(0.4x-1.2)+0.36x=0.6
0,12x-0,36+0,36x=0,6
0,48x=0,96/:0,48
x=2

e)(3x-1) (2x+7)=6x²+31
6x²+21x-2x-7=6x²+31
19x=38/:19
x=2
f)3x²-(3x+2)(x-1)=8
3x²-3x²+3x-2x+2=8
x=8-2
x=6
g)9x+6-(3x-4)(x+2)=36-3x²
9x+6-3x²-6x+4x+8=36-3x²
7x+14=36
7x=22/:7
x=22/7=3 1/7
h)7(2x-5)-[5(7x-2)-2(5x-7)]=-72
14x-35-(35x-10-10x+14)=-72
14x-35-25x-4=-72
-11x=-72+39
-11x=-33/:(-11)
x=3
2009-12-01T19:40:11+01:00
8(7-4y)-7(4y+1)+5(8y-1)=19
56-32y-28y-7+40y-5=19
-32y-28y+40y=19+5-56
-20y=-32
y=-32:(-20)
y=1,6

3(2x+1)-5(12x-7)+7(6x-1)=23
6x+3-60x+30+42x-7=23
6x-60x+42x=23+7-30-3
-2x=-3
x=-3:(-2)
x=1,5

0.2x+0.5x+5(5x-1)-2.7x=6.5
0.2x+0.5x+25x-5-2,7x=6,5
0.2x+0.5x+25x-2,7x=6,5+5
23x=11,5
x=11,5:23
x=0,5

0.3(0.4x-1.2)+0.36x=0.6
0,12x-0,36+0.36x=0.6
0,12x+0.36x=0.6+0,36
0,48x=0,96
x=0,96:0,48
x=2

(3x-1) (2x+7)=6x²+31
6x²+21x-2x-7=6x²+31
6x²-6x²+21x-2x=31+7
19x=38
x=38:19
x=2

3x²-(3x+2)(x-1)=8
3x²-3x²+3x+2x-2=8
3x+2x=8+2
5x=10
x=10:5
x=2

9x+6-(3x-4)(x+2)=36-3x²
9x+6-3x²-3x-4x-8=36-3x²
-3x²+3x²+9x-3x-4x=36-6+8
9x-3x-4x=38
2x=38
x=38:2
x=19

7(2x-5)-[5(7x-2)-2(5x-7)]=-72
14x-35-[35x-10-10x+14]=-72
14x-35-35x+10+10x-14=-72
14x-35x+10x=-72+35-10+14
-21x=-13
x=-21:(-13)
x=1,6


2 5 2